Fabrication And Characterization Of Tri-Layer Lightweight Ceramic Tile - Ooi, Chia Ying (Universiti Sains Malaysia, 2017)
This study describes the fabrication process of tri-layered lightweight ceramic tiles, formed from three layers with dense structure at upper and lower layers and porous structure at middle layer, which helps the weight reduction of tile. The parameter studied were the effect of tri-layer ratio and firing temperature on fabrication of tri-layer lightweight ceramic tile. 5 wt% of calcium carbonate (CaCO3) was introduce into the ceramic tile formulation in order to produce porous structure middle layer. The ceramic powder and CaCO3 was characterized. X-Ray Fluorescence (XRF), Field Emission Scanning Electron Microscope (FESEM) and X-Ray Diffraction (XRD) were used to analyse the chemical composition, morphology and phase composition while Thermogravimetry- Differential Thermal Analysis (TG-DTA) was used to determine the thermal behaviour of these powder. Optical micrograph for cross section of tri-layer lightweight ceramic tile indicate that good interfacial bonding between the layers were obtained. Also, thermal expansion coefficient of green bodies and sintered sample shows that there is no thermal mismatch issue exist. This information indicates that the incorporation of CaCO3 powder in the middle layer formula for sintered ceramic tile reduced weight of ceramic tile by 7.3% (1150 oC) and 3.7% (1050 oC). Also, the mechanical strength of the lightweight ceramic tiles were reduced when increasing the layer ratio of the porous structure middle layer. Therefore, tri-layer pressing approach is suitable candidate method for the fabrication of lightweight ceramic tile.